Normas Voluntárias de Sustentabilidade (NVS) e implicaç\~oes sobre as exportaç\~oes de produtos do agronegócio: Soja - Alicia Cechin; Marcelo José Braga Nonnenberg (Instituto de Pesquisa Econômica Aplicada (IPEA), 2023)
– This study analyzed the dynamics of the Brazilian soybean production chain, with the aim of understanding the position of producers/exporters in the sector in terms of production, foreign markets and the environment. In addition, the soy certification process through adherence to the voluntary sustainability standards (NVS) and the relevance of this new form of market regulation were added to the discussion. A bibliographic review was carried out on the subject, starting with the mapping of the Brazilian soybean production chain and Brazil's position in the international scenario, relating the role of certifications in managing the effects of production on the environment. For this second stage, relevant information was collected from producers, exporters and companies that certify Brazilian soy. It should be noted that only two certifications stand out in this production chain, ProTerra and mainly the Round Table Responsible Soy (RTRS). The results show the importance of creating the Soy Moratorium in Brazil, which focuses on the preservation of the Amazon, reflected by the commitment not to sell or finance soy produced in deforested areas in this region. With regard to certification, interviews with producers, certifiers and associations showed that these agents are aware of the need to adopt certificates and the diversity of options available on the market. In addition, they elucidate the importance of having certification, both for environmental preservation and for accessing the most demanding markets, such as the European Union, thereby obtaining a higher price for your product.
Keywords: F18; F13; Q17; 330; soy; export; trade; voluntary sustainability standards (NVS); certification